Robot orientation with histograms on MSL - Ribeiro, A. Fernando (2012)
One of the most important tasks on robot soccer is localization. The team robots should self-localize on the 18 x 12 meters soccer field. Since a few years ago the soccer field has increased and the corner posts were removed and that increased the localization task complexity. One important aspect to take care for a proper localization is to find out the robot orientation. This paper proposes a new technique to calculate the robot orientation. The proposed method consists of using a histogram of white-green transitions (to detect the lines on the field) to know the robot orientation. This technique does not take much computational time and proves to be very reliable.